Assessing the performance of electrospun nanofabrics as potential interlayer reinforcement materials for fiber-reinforced polymers - Loizou, Katerina; Evangelou, Angelos; Marangos, Orestes; Koutsokeras, Loukas E.; Chrysafi, Iouliana; Yiatros, Stylianos; Constantinides, Georgios; Zaoutsos, Stefanos; Drakonakis, Vassilis (My University, 2021)
Multiscale-reinforced polymers offer enhanced functionality due to the three different scales that are incorporated; microfiber, nanofiber, and nanoparticle. This work aims to investigate the applicability of different polymer-based nanofabrics, fabricated via electrospinning as reinforcement interlayers for multilayer-fiber-reinforced polymer composites. Three different polymers are examined; polyamide 6, polyacrylonitrile, and polyvinylidene fluoride, both plain and doped with multiwalled carbon nanotubes (MWCNTs). The effect of nanotube concentration on the properties of the resulting nanofabrics is also examined. Nine different nanofabric systems are prepared. The stress–strain behavior of the different nanofabric systems, which are eventually used as reinforcement interlayers, is investigated to assess the enhancement of the mechanical properties and to evaluate their potential as interlayer reinforcements. Scanning electron microscopy is employed to visualize the morphology and microstructure of the electrospun nanofabrics. The thermal behavior of the nanofabrics is investigated via differential scanning calorimetry to elucidate the glass and melting point of the nanofabrics, which can be used to identify optimum processing parameters at composite level. Introduction of MWCNTs appears to augment the mechanical response of the polymer nanofabrics. Examination of the mechanical performance of these interlayer reinforcements after heat treatment above the glass transition temperature reveals that morphological and microstructural changes can promote further enhancement of the mechanical response.
Keywords: Electrospun nanofabrics; Fiber-reinforced polymers; Interlayer; Nanofibers